2021
DOI: 10.1177/14799731211056092
|View full text |Cite
|
Sign up to set email alerts
|

Title: Blood flow restricted exercise training: Perspectives of people with chronic obstructive pulmonary disease and health professionals

Abstract: Objective This descriptive qualitative study explored perspectives of people with chronic obstructive pulmonary disease (COPD) and health professionals concerning blood flow restricted exercise (BFRE) training. Methods People living with COPD and health professionals (exercise physiologists, physiotherapists, and hospital-based respiratory nurses and doctors) participated in interviews or focus groups, which included information about BFRE training and a facilitated discussion of positive aspects, barriers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There is a growing body of literature to support the utility of BFR exercise for specific patients, including those with multiple sclerosis (13), rheumatoid arthritis (25), sporadic inclusion body myositis (11), chronic kidney disease (26), and following anterior cruciate ligament surgery (30), along with promising case reports for patients with Parkinson's disease (7) and sarcopenia (17). Interview and focus group data indicate that patients with chronic obstructive pulmonary disease and their health care professionals have positive perceptions of using BFR exercise for health benefits; however, further evidence of the suitability and appropriate prescription of BFR for specific conditions is still required (23).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature to support the utility of BFR exercise for specific patients, including those with multiple sclerosis (13), rheumatoid arthritis (25), sporadic inclusion body myositis (11), chronic kidney disease (26), and following anterior cruciate ligament surgery (30), along with promising case reports for patients with Parkinson's disease (7) and sarcopenia (17). Interview and focus group data indicate that patients with chronic obstructive pulmonary disease and their health care professionals have positive perceptions of using BFR exercise for health benefits; however, further evidence of the suitability and appropriate prescription of BFR for specific conditions is still required (23).…”
Section: Discussionmentioning
confidence: 99%
“…Modified exercise training techniquesgetting the patient's view November 25th, 2021 The pulmonary rehabilitation literature is littered with studies investigating novel training methodologies aimed at enhancing efficacy and/or comfort for people undertaking rehabilitation. In many cases the focus of such investigations is the clinical outcome of the intervention but in the journal this month, Pereira-Neto et al 5 provide a welcome insight into the patient and therapist perspective of one such methodology, blood flow restricted exercise. They highlight potential concerns about safety, supervision and location of treatment among patients with chronic respiratory disease.…”
Section: Crd Editor's Corner Archive: October-december Michael C Steinermentioning
confidence: 99%
“…16 A recent descriptive qualitative study showed that patients with COPD and health professionals recognized BFR-RE with low load as an alternative exercise method with potential health benefits since the adherence of training might be compromised by the traditional high load and showed concerns on the adverse events during BFR-RE. 17 A review demonstrated the sideeffects were minimal and the cardiovascular complications were not elevated by BFR with appropriate application by trained practitioners after careful case selection and contraindication screening. 18 The effect of BFR-RE on muscle strength in hospitalized patient with post-COPDAE, which has not been studied, was the primary outcome of this study.…”
Section: Introductionmentioning
confidence: 99%